PENGUJIAN SKALA PENUH DAN ANALISIS PERKUATAN CERUCUK MATRAS BAMBU UNTUK TIMBUNAN BADAN JALAN DI ATAS TANAH LUNAK DI LOKASI TAMBAK OSO, SURABAYA - Irsyam, Masyhur; Krisnanto, Sugeng (Civil Engineering Forum Teknik Sipil, 2008)
Bamboo pile-mattress was proposed as an alternative ground reinforcement to support road embankment on soft soils for the Surabaya Eastern Ring Road Project. A full scale test program was performed to investigate reliability of the reinforcement system since standard calculation for this type of construction was not available. The full scale program was consisted of ground settlement monitoring by settlement plates and pore water pressure monitoring by piezometers. Readings were taken for each stage of embankment construction. Analytical and numerical analyses were also performed to verify the full scale test results. Analytical calculation for immediate settlement was performed based on the elasticity theory, for consolidation settlement was performed by the 1-D Terzaghi’s consolidation theory. Numerical calculation was performed using the finite element method utilizing a commercial software package called PLAXIS. In the finite element analyses, subsurface soil and embankment were modeled as elastic-plastic solid materials using the Mohr-Coulomb failure criteria. Bamboo piles and mattress were modeled as elastic-plastic springs and elastic-plastics beams, respectively. Monitoring records and analysis results show that bamboo pile-mattress reinforcement has effectively increased stability. Consolidation settlement was found to be relatively uniform. Results also show that monitoring records and analysis results are relatively similar.